Thermal Comfort Assessment of Temporary Shelters Used in Türkiye by CFD Analysis - Gülten, Ayça; Yolacti, Seval (International Journal of Architectural Engineering Technology, 2025)
This research assessed the thermal comfort conditions of temporary shelters in Türkiye using the Predicted Mean Vote (PMV) index. A typical container-type shelter was selected as the model for the analysis. Simulations were conducted on July 21 at four different times: 10:00, 12:00, 14:00, and 16:00. The Computational Fluid Dynamics (CFD) software Ansys Fluent was utilized to perform the simulations. Eight shelters positioned in various parts of a standard shelter layout were analyzed. Two ventilation scenarios were considered: one with only the doors open, and another with both doors and windows open. While PMV quantifies the average thermal sensation on a scale from -3 (cold) to +3 (hot), in Scenario 1, the general scale of PMV is hot or exceeds the hot scale; besides, the number of situations classified as warm and slightly warm in Scenario 2 increases. In Scenario 1, PMV values were generally high and surpassed the thermal comfort threshold (+3-hot), especially during the morning and midday hours, while natural ventilation improved significantly, leading to lower PMV values, which are about +2(warm), and enhanced thermal comfort in Scenario 2. As a result, it is recommended to consider site-specific orientation, prioritizing layouts that maximize exposure to prevailing wind directions, particularly for living and sleeping areas, while also minimizing the exposure of heavily occupied zones to intense solar radiation.